The Development of Ecobites Pimnas-37 Booklet as English Learning Media in Teaching Writing Descriptive Text - Sabrina Mutiara Sari; Esti Kurniasih (Raja Zulkarnain Education Foundation, 2026)
The results of this study indicate that the Ecobites Pimnas-37 booklet, developed as an English learning medium, was systematically designed to support vocational high school students in improving their descriptive writing skills. This study employed a Research and Development (R&D) method based on the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. In the analysis stage, students’ needs and difficulties in writing descriptive texts were identified, particularly in organizing ideas, using appropriate vocabulary, and constructing grammatically correct sentences. The design stage focused on determining learning objectives, writing indicators, and the booklet structure. The development stage involved producing the Ecobites Pimnas-37 booklet by integrating English for Specific Purposes (ESP) principles with an eco-based learning approach. The implementation stage involved applying the booklet in classroom learning activities to facilitate students’ practice in writing descriptive texts. Students’ writing performance was measured using several indicators, including the ability to identify the generic structure of descriptive texts (identification and description), use appropriate vocabulary, apply simple present tense correctly, and develop clear and coherent descriptions of objects related to environmental topics. The evaluation stage was conducted through expert validation and feedback to assess the quality and feasibility of the booklet as an instructional medium. The validation results showed that the Ecobites Pimnas-37 booklet was categorized as very good and suitable for use in English learning. Overall, the booklet demonstrates strong potential as a valid and practical medium for teaching descriptive writing in vocational high schools.